EFFECT OF GREENLEAF QUALITY AND MOISTURE CONTENT ON PHYSICAL AND ORGANOLEPTIC OF THE CTC (Crushing Tearing Curling) TEA - Hafiz Thanoza; Devi Silsia; Zulman Efendi (BPFP Faperta UNIB, 2016)
PTPN VII (Persero) Pagaralam Business Unitstarted developing the processing of black tea (CTC). Only after several times the processing quality CTC teas produced unsatisfactory. The Company continues to optimize the performance ofthe processingand quality control of CTC tea. This study aims to determine the effect of the quality of shootsandwilting percentage of the physical and organoleptic properties of CTC tea. This research was conducted in PTPN VII (Persero) Act Pagaralam. The results showed that all of the top quality withvalue range 62% to 70% and the percentage of wilted 65% to 72% no real effect on the physical and organoleptic properties. The water content and density of CTC tea has fulfilled SNI and enterprise standards. CTC tea produced medium quality (Fair made).